Service Quality, Product Quality, and Customer Satisfaction as Predictors of Customer Loyalty: Evidence from an Internet Service Provider in Indonesia - Yogo Prawiro Derijo; Agus Setyo Pranowo; Sufrin Hannan (International Journal Administration, Business & Organization, 2026)
This study investigates the influence of service quality and product quality on customer loyalty, specifically examining the mediating role of customer satisfaction within the context of an Indonesian Internet Service Provider (ISP). Adopting a quantitative approach, the research utilizes Structural Equation Modeling (SEM) to analyze data obtained through proportional random sampling. The analytical framework incorporates confirmatory factor analysis and Sobel mediation testing to ensure a rigorous evaluation of the proposed model. The findings demonstrate that both service quality and product quality significantly influence customer satisfaction, which in turn serves as a strong predictor of customer loyalty. Furthermore, customer satisfaction is found to partially mediate the relationship between these quality dimensions and loyalty. These results offer theoretical advancement in understanding loyalty formation within emerging digital markets and provide practical guidance for ISPs to enhance retention strategies through integrated quality improvements. This research contributes novel empirical evidence on the joint effects of service and product quality in developing digital service environments, effectively addressing existing literature gaps regarding the mediation mechanisms that drive customer loyalty.